Difficult orotracheal intubation in dogs and cats. Issue 2 (3rd February 2017) - Mathis, Alessandra
Abstract : In veterinary practice, difficult orotracheal intubation is an uncommon occurrence but it can be a life‐threatening situation. Arduous tracheal intubation can occur for a number of reasons, sometimes unknown to the veterinary surgeon until the patient is anaesthetised. This article explores the causes of difficult orotracheal intubation and how to prepare for this type of situation, as well as describing how to proceed in the case of a difficult, or even seemingly impossible, orotracheal intubation.